Military Tribunate in the Careers of Roman Senators of the Severan Period. Part 2: Special Distinctions (Dona Militaria, Adlectiones, Commendatio Augusti) - Okoń, Danuta (Polskie Towarzystwo Filologiczne, 2020)
In this article, the second in a series devoted to the office of the military tribune in the senatorial cursus honorum in the Severan period, the following findings are presented: (1) in the group of 123 military tribunes from the Severan period who subsequently became senators, special distinctions (dona militaria, adlectio, commendatio) were awarded to 49 people (approx. 40%); (2) dona militaria were granted to 8 of them; most people from this group are attested as homines novi and came from the provinces; (3) the gradual disappearance of references to dona in the source material may be the result of the intentional damage of inscriptions relating to emperors as award givers (e.g., due to the damnatio memoriae) or a change in the character of these distinctions (financial rewards replacing the traditional dona); (4) dona did not have any greater impact on the subsequentadlectio or commendatio; they did not become a part of the senatorial mode of promotion; (5) we know of 23 former tribunes who were adlected among the former magistrates; homines novi and provincials were the most numerous among them; (6) we know of 28 former tribunes who became candidati Augusti for magistracies; representatives of gentes senatoriae and residents of Italy were the most numerous among them; (7) candidati were people from the senatorial order, whereas adlecti were people from various orders; (8) in the group of 49 senators with special distinctions that was analysed, those distinguished once and twice dominate.